A new limonoid from stem bark of Chisocheton pentandrus (Meliaceae). Issue 21 (2nd November 2018) - Supriatno,; Nurlelasari,; Herlina, Tati; Harneti, Desi; Maharani, Rani; Hidayat, Ace Tatang; Mayanti, Tri; Supratman, Unang; Azmi, Mohamad Nurul; Shiono, Yoshihito
Abstract: A new limonoid, pentandricine (1 ), along with three known limonoids, ceramicine B (2 ), 6-de(acetyloxy)-23-oxochisocheton (3 ), 6-de(acetyloxy)-23-oxo-7- O -deacetylchisocheton (4 ), have been isolated from the stembark of Chisocheton pentandrus . The chemical structures of the new compound were elucidated on the basis of spectroscopic evidence. All of the compounds were tested for their cytotoxic effects against MCF-7 breast cancer cells. Compounds1 –4 showed weak and no cytotoxicity against MCF-7 breast cancer cells with IC50 values of 369.84, 150.86, 208.93 and 120.09 μM, respectively. Abstract :